Structural analysis of an InGaN/GaN based light emitting diode by X-ray diffraction - Öztürk, M. K.; Hongbo, Y.; Sarikavak, B.; Korçak, S.; Özçelik, S.; Özbay, E. (Springer Science and Business Media LLC, 2009)
The important structural characteristics of hexagonal GaN in an InGaN/GaN multi quantum well, which was aimed to make a light emitted diode and was grown by metalorganic chemical vapor deposition on c-plain sapphire, are determined by using nondestructive high-resolution X-ray diffraction in detail. The distorted GaN layers were described as mosaic crystals characterized by vertical and lateral coherence lengths, a mean tilt, twist, screw and edge type threading dislocation densities. The rocking curves of symmetric (00.l) reflections were used to determine the tilt angle, while the twist angle was an extrapolated grown ω-scan for an asymmetric (hk.l) Bragg reflection with an h or k nonzero. Moreover, it is an important result that the mosaic structure was analyzed from a different (10.l) crystal direction that was the angular inclined plane to the z-axis. The mosaic structure parameters were obtained in an approximately defined ratio depending on the inclination or polar angle of the sample.
Keywords: Structural characteristics; Rocking curves; Light; Non destructive; Tilt angle; X ray diffraction; High resolution X ray diffraction; Structural analysis; Screw dislocations; Metalorganic chemical vapor deposition; GaN layers; Machinery; Coherence lengths; Semiconductor quantum wells; Inclined planes; Twist angles; Hexagonal GaN; Bragg reflection; Crystal direction; Laser optics; X ray diffraction analysis; Gallium alloys; Gallium nitride; Mosaic crystals; Light emitting diodes; Physical optics; Polar angles; InGaN/GaN; InGaN/GaN multi-quantum well; Threading dislocation densities; Edge dislocations; Mosaic structure